The Role of miRNAs in Asthma - Tosun, Hilal; Ceylan, Hamid (International Conference on Applied Engineering and Natural Sciences, 2023)
Asthma is a heterogeneous respiratory disease that causes cough and respiratory distress and is known to greatly affect the quality of life in the later stages. In asthma, as in all other inflammatory diseases, miRNAs control the cell’s ability to grow, reproduce, and survive by regulating the interactions of cells that shape the bronchi, airway structure, and cells responsible for defense mechanisms in the lungs. In addition, miRNAs play an active role in synthesizing and secreting immune mediators and chemokines. More importantly, they are molecules with chemical and biological properties that allow patients to be classified for optimal drug selection, can be used as appropriate biomarkers for diseases, and simplify clinical management. At the same time, these molecules ease the burden of intensive care associated with diseases, while reducing the economic burden of the disease. In this review, we discussed the interrelationships between miRNAs and asthma pathologies as well as the effect of miRNAs on the disease trajectory in asthma.